Word Order of Noun Phrase by Modification in Mambwe Language - Pethias Siame (PT Mattawang Mediatama Solution, 2023)
Mambwe language is spoken in Mbala and Senga districts in Northern Province along the corridors of Zambia and Tanzania. Guthrie (1948) classifies Mambwe as M15. Nurse and Phillipson (1999) have characterized Mambwe as emanating from a language called Fipa in Southern Tanzania. Nurse and Phillipson (1999) add that most speakers of Mambwe language are found on the Zambian side. This article presents an analysis of the syntactic structure of the word of the noun phrase (NP) by modification in Mambwe language. The paper is underpinned by Lexical Morphology (LM) and Bantu Morpho-syntax theoretical frameworks. The study used qualitative approach, elicitation and document analysis methods for data collection and analysis. The paper identifies the modifiers which are prevalent in Mambwe and analyses how they combine with nouns to form the NP. It also outlines the prevailing word orders in the NP by modification in Mambwe language. The study shows that there are three common word orders in the NP by modification in Mambwe language, namely; Noun + Demonstrative (N+Dem), Noun + Adjective (N+Adj) and Possessive Pre-prefix + Adjective (Poss. Pre-prefix +Adj).